1991
DOI: 10.1111/j.1365-2826.1991.tb00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Peripherally Administered Exerts Somatostatin‐Releasing Action in the Conscious Rat

Abstract: This study was designed to determine whether glutamate is able to stimulate somatostatin release from in vivo conscious animals when somatostatin release is monitored in unanaesthetized rats stereotaxically implanted with a push-pull cannula in the median eminence. One week after implantation, the median eminence was perfused with artificial cerebrospinal fluid alone or with the addition of either CGS 19755, an N-methyl-D-aspartate (NMDA) receptor antagonist M). The latter (which is able to cross the brain-blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Finally, compared with that in normal boys, the GHRH response to -dopa stimulation is less in naturally androgen-deficient individuals with idiopathic delayed puberty (Argente et al 1987, Liapi et al 1988, whereas administration of oxandrolone to these patients significantly increases the -dopa induced GHRH release (Liapi et al 1988). NMA has previously been reported to stimulate the release of somatostatin in the median eminence in vivo (Benyassi et al 1991) and from cultured hypothalamic neurones in vitro (Rage et al 1993). Furthermore, NMDA induces a significant increase in somatostatin mRNA levels and the noncompetitive NMDA antagonist MK 801 has been shown to reduce somatostatin mRNA content significantly in cultured hypothalamic neurones in vitro (Rage et al 1994).…”
Section: Discussionmentioning
confidence: 89%
“…Finally, compared with that in normal boys, the GHRH response to -dopa stimulation is less in naturally androgen-deficient individuals with idiopathic delayed puberty (Argente et al 1987, Liapi et al 1988, whereas administration of oxandrolone to these patients significantly increases the -dopa induced GHRH release (Liapi et al 1988). NMA has previously been reported to stimulate the release of somatostatin in the median eminence in vivo (Benyassi et al 1991) and from cultured hypothalamic neurones in vitro (Rage et al 1993). Furthermore, NMDA induces a significant increase in somatostatin mRNA levels and the noncompetitive NMDA antagonist MK 801 has been shown to reduce somatostatin mRNA content significantly in cultured hypothalamic neurones in vitro (Rage et al 1994).…”
Section: Discussionmentioning
confidence: 89%
“…These different regulations could be explained either by a differential expression of glutamate receptors in different cellular populations presenting only some promoters or by different glutamate receptors involved in the regulation of BDNF promoters. Indeed, previous studies have demonstrated the critical role played by glutamate through NMDA (Tapia‐Arancibia et Astier, 1988; Benyassi et al, 1991; Gu et al, 1999) and non‐NMDA ionotropic (van den Pol et al, 1990) or metabotropic receptors in the hypothalamus, both in the developing and in the adult brain (van den Pol et al, 1994, 1995; Ghosh et al, 1997). Moreover, a developmentally regulated expression of NMDA (Rage et al, 1994) or metabotropic glutamate receptors in the hypthalamus has been reported (Ghosh et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…That NMA may not affect GHRH neurons directly could be inferred from a recent observation (25) that some excitatory actions of NMA are mediated by norepinephrine, which has previously been shown to be a GHRH secretagogue in rats (28). On the other hand, NMDA receptor activation has also been shown to lead to an increase in somatostatin release in the median eminence (29) and from hypothalamic neurons in vitro (30,31). It may therefore, be possible, as has been proposed for NMDAregulated PRL secretion (21,32) that NMDA receptor mediated neurotransmission alters both the GHRH and somatostatin rclease and the net GH secretion depends on the ratio of existing NMDA drives to the GHRH/somatostatin neurons.…”
Section: Discussionmentioning
confidence: 99%